2021
DOI: 10.3390/coatings11070780
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Reverse Potential Electrodeposition of Carbon-Free Ni/NiO Nanocomposite Thin Film Electrode for Energy Storage Supercapacitor Electrodes

Abstract: A combined cyclic voltammetry and pulse reverse potential electrodeposition technique has been used to synthesize carbon-free Ni/NiO nanocomposite thin film supercapacitor electrode. The structural and morphological analyses have revealed the presence of crystalline phases of both Ni and NiO in the form of nanospheres of size ~ 50 nm. The electrochemical analysis of the Ni/NiOna nocomposite electrode has shown a remarkable performance by delivering a high specific capacitance of 2000 Fg−1 at an applied current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The wavenumber ranges of these absorption bands were also similar to those reported in the literature. 19 It was found that no obvious absorption peaks belonging to crystalline Co 3 O 4 species were observed in the IR spectra of the Co-300 and Co-400 catalysts. This may be due to the possible low-intensity absorption of amorphous Co 3 O 4 in visible light.…”
Section: Resultsmentioning
confidence: 89%
“…The wavenumber ranges of these absorption bands were also similar to those reported in the literature. 19 It was found that no obvious absorption peaks belonging to crystalline Co 3 O 4 species were observed in the IR spectra of the Co-300 and Co-400 catalysts. This may be due to the possible low-intensity absorption of amorphous Co 3 O 4 in visible light.…”
Section: Resultsmentioning
confidence: 89%
“…The XRD patterns of the NF substrate and the various thin films deposited on the NF substrates are presented in Figure 1A (I To understand the growth mechanism of these films, investigation was carried out by depositing the same on titanium substrates as reported in our recent work on Ni-NiO and Co-Co 3 O 4 20,27 and these results have been provided in the Supporting Information Data (Figure S1a). It is to be noted that on titanium substrate (Figure S1a), the peaks of Co (100 S1b).…”
Section: Resultsmentioning
confidence: 99%
“…To understand the growth mechanism of these films, investigation was carried out by depositing the same on titanium substrates as reported in our recent work on Ni‐NiO and Co‐Co 3 O 4 20,27 and these results have been provided in the Supporting Information Data (Figure S1a). It is to be noted that on titanium substrate (Figure S1a), the peaks of Co (100) and Co (101) planes of the hexagonal crystal structure of cobalt (JCPDS card No‐00‐005‐0727), Co 3 O 4 (222) and Co 3 O 4 (400) plane of the cubic crystal structure of Co 3 O 4 (JCPDS card No‐42‐1467) can be detected at 2 θ of 41.7°, 47.5°, 38.5°, and 44.5°, respectively, in the XRD spectrum of the Co‐Co 3 O 4 composite thin film.…”
Section: Resultsmentioning
confidence: 99%
“…The layered structure of stacked MXene's nanosheet shape reduces active surface availability to electrolytes, while open but limited intermediate region promotes quick ion intercalation and high-density energy storage, meeting the requirements for intercalation pseudocapacitance. [31,32] TMDs are also interesting pseudocapacitive possibilities because of their large interlayer gaps, which lead to rapid ion transport. For example, layer-bylayer VS 2 stacked nanosheets might offer a robust basis for volume swelling/shrinkage when an ion is inserted/extracted, resulting in long-term cycle stability following the reaction: VS 2 + xNa + + xe − → Na x VS 2.…”
Section: Electrochemical Capacitorsmentioning
confidence: 99%